Anda di halaman 1dari 1

1) Usando los teoremas del algebra de BOOLE, simplificar las funciones siguientes:

a) F= W.X.Y.Z (W.X.Y.Z + W.X.Y.Z + W.X.Y.Z + W.X.Y.Z)


F= W.W.X.X.Y.Y.(Z.Z) + W.W.(X.X).Y.Y.Z.Z + (W.W).X.X.Y.Y.Z.Z + W.W.X.X.(Y.Y).Z.Z
F= W.W.X.X.Y.Y.(0) + W.W.(0).Y.Y.Z.Z + (0).X.X.Y.Y.Z.Z + W.W.X.X.(0).Z.Z
F= 0 + 0 + 0 + 0 = 0

b) F=A.B + A.B.C.D + A.B.D.E + A.B.C.E + C.D.E


F=A.B.(1 + C.D + D.E + C.E) + C.D.E
F=A.B.(1 + C.(D + E) + D.E) + C.D.E
F=A.B.(D + D + C.(D + E) + D.E) + C.D.E
F=A.B.(D.(1 + E) + C.D + C.E + D) + C.D.E
F=A.B. (D.(1) + C.D + C.E + D) + C.D.E
F=A.B. (D.(1 + C) + C.E + D) + C.D.E
F= A.B. (D.(1) + C.E + D) + C.D.E
F= A.B. (1 + C.E) + C.D.E
F= A.B. (C + C + C.E) + C.D.E
F= A.B. (C + C(1 + E)) + C.D.E
F= A.B. (C + C) + C.D.E
F= A.B + C.D.E

c) F=M.N.O + Q.P.N + P.R.M + Q.O.M.P + M.R


F=M.O.(N + PQ) + Q.P.N + M.R.(1 + P)
F=M.O.(N + (N + N).PQ) + Q.P.N + M.R.(1)
F=M.O.(N + N.PQ + N.P.Q) + Q.P.N + M.R.(1)
F=M.O.(N + N.P.Q) + Q.P.N + M.R
F=M.O.N + M.O.N.P.Q + Q.P.N + M.R
F=M.O.N + N.P.Q.(M.O + 1)+ M.R
F=M.O.N + N.P.Q.(1) + M.R
F=M.(ON + R) + N.P.Q